Planning-technological concept of one and multiple-built construction objects of multifunctional appointment on the principles of modularity - Shpakovа, А. (Ways to Improve Construction Efficiency, 2019)
The article deals with the formation of the main provisions of the planning and technological concept of point building of urban land plots taking into account the concepts of the life cycle of objects and the unstable situation in the market of commercial and residential real estate. The author proposes to use a sound plan scheme with the possibility of creating modular variable parts of the building, depending on the situation on the real estate market, the goals and objectives of the developer of the construction project.